2014
DOI: 10.4103/0189-6725.132803
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of radiological investigations with clinical findings in cases of abdominal mass in the paediatric age group

Abstract: Most of the cases of abdominal mass can be well evaluated clinically in terms of the diagnosis and organ of origin. Both radiological investigation and a good clinical examination have equal sensitivity. Radiological investigations are thus only adjuvant to a good clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…In a similar study conducted at Aga Khan University Hospital, Karachi, Jawaid et al (17) predominance among such children with male to female ratio of 1.5:1. Our results also match with those of Indian studies where Gupta et al (18) (2018) and Mohan et al (19) (2017) observed comparable higher proportion of under 5 year age group and reported it to be 58.0% and 59.9% respectively while Khan et al (20) (2015) and Sharma et al (21) (2014) reported similar male predominance with male to female ratio of 1.9:1 and 2:1 respectively among such children. In a similar study involving Iranian children with adnominal mass, Zareifar et al (22) (2016) reported comparable mean age of 4.8±4.2 years with similar higher proportion of males (1.9:1) and under 5 years age group (62.4%).…”
Section: Discussionsupporting
confidence: 91%
“…In a similar study conducted at Aga Khan University Hospital, Karachi, Jawaid et al (17) predominance among such children with male to female ratio of 1.5:1. Our results also match with those of Indian studies where Gupta et al (18) (2018) and Mohan et al (19) (2017) observed comparable higher proportion of under 5 year age group and reported it to be 58.0% and 59.9% respectively while Khan et al (20) (2015) and Sharma et al (21) (2014) reported similar male predominance with male to female ratio of 1.9:1 and 2:1 respectively among such children. In a similar study involving Iranian children with adnominal mass, Zareifar et al (22) (2016) reported comparable mean age of 4.8±4.2 years with similar higher proportion of males (1.9:1) and under 5 years age group (62.4%).…”
Section: Discussionsupporting
confidence: 91%
“…Preoperative diagnosis is usually done with the use of imaging modalities such as ultrasonography, CT scan and or MRI [11,12]. While MRI is the most accurate investigation in diagnosing a cysts, ultrasounds and CT scan can readily distinguish between solid and cystic masses [13,14].…”
Section: Discussionmentioning
confidence: 99%